Green coffee ameliorates components of diet-induced metabolic syndrome in rats. (June 2019) - Bhandarkar, Nikhil S.; Mouatt, Peter; Brown, Lindsay; Panchal, Sunil K.
Graphical abstract: Highlights: Green coffee attenuated body weight gain and normalised systolic blood pressure. Green coffee reduced cardiac and hepatic inflammation. Dyslipidaemia and glucose tolerance were unchanged by green coffee extracts. Chlorogenic acid, trigonelline and diterpenoids could be the bioactive components. Abstract: Metabolic syndrome, especially obesity, increases the risk of type 2 diabetes and cardiovascular disease. We hypothesised that green coffee will attenuate metabolic, cardiovascular and liver parameters in high-carbohydrate high-fat diet-fed rats. Male Wistar rats (8–9 weeks old) were divided into 6 groups and fed for 16 weeks with either corn starch diet (C), C with either 5% green or decaffeinated green coffee in food for the last 8 weeks, high-carbohydrate high-fat diet (H) or H with either 5% green or decaffeinated green coffee in food for the last 8 weeks. Green coffee contained chlorogenic acids, trigonelline, caffeine and diterpenoids; decaffeinated green coffee contained these compounds but no caffeine. Green coffee attenuated body weight, systolic blood pressure, inflammation in the heart and liver and diastolic stiffness without improving glucose sensitivity or plasma lipids. We suggest that chlorogenic acids, trigonelline and diterpenoids in green coffee attenuate diet-induced abnormalities in heart and liver.